EFEKTIFITAS PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM PEMBELAJARAN (PENELITIAN DI SMA NEGERI 2 SUKOHARJO) - -, Sutoyo (UNIVERSITAS SLAMET RIYADI, 2016)
This research aims at (1) identifying whether the teachers already utilizing informationtechnology in teaching or not (2) identifying the factors influencing the usage of the technology inteaching (3) identifying the effectifity of the usage of the technology in teaching.This research is a qualitative research conducted in SMA Negeri 2 Sukoharjo. Thetechnique applied in data collecting is quetioners, observation and interview, quetioner is used tocollect the data about the teachers competence in applying information technology in teaching.Interview and observation is used for collecting the data about the factors influencing the usageof the technology in teaching as well as the effectifity of the usage.The result shows that (1) in general, the teachers already apllied information technology inteaching process (2) in applying information technology, the teachers competence andinfrastructure such as computer, LCD and internet connection is needed (3) the teachie withinformation technology is very effective. It is because this improve the students focul in learning.Keywords: effectivity, information technology, teaching and learning